Relapse of Takayasu arteritis as a cause of suicidal poisoning and subsequent major ischemic stroke successfully treated with thrombolytic therapy - Komatina, Nenad; Lepić, Toplica; Labović, Boban; Stevović, Tatjana; Petronijević, Milan; Radovinović Tasić, Sanja; Obradović, Dragana (Vojnosanitetski pregled, 2017)
Introduction. Takayasu arteritis (TA) is a rare large vessel arteritis, affecting primarily aorta and its major branches. Its clinical manifestations can vary significantly – from asymptomatic to serious vascular events. Acute neurological complications are frequent at the onset of the disease and in relapses. Anxiety and depression are more frequent in TA patients than in general population as well as during relapses. Prevalence of transient ischemic attack or ischemic stroke in TA patients is approximately 10–20%. Case report. We presented a patient with TA that began with a depressive episode resulting in attempted suicide by bromazepame poisoning. This was subsequently followed by major ischemic stroke caused by thrombosis of the left middle cerebral artery (probably due to aortic arch embolism) successfully treated with intravenous thrombolysis. Conclusion. Intravenous thrombolysis appears to be safe and effective in patients with TA and stroke.
Keywords: takayasu arteritis; recurrence; poisoning; suicide; attempted; thrombosis; middle cerebral artery; tissue plasminogen activator; treatment outcome; depression